Efficacy of ormeloxifene versus norethisterone in the management of abnormal uterine bleeding - Mainani, Aishwarya; Vishwekar, Pallavi; Shah, Jui; Shetty, Chiranjeev; Singh, Garima; More, Mayuri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Abnormal uterine bleeding (AUB) is a common gynecological issue that significantly affects the quality of life of women, particularly those in the reproductive and perimenopausal age groups. Ormeloxifene, a selective estrogen receptor modulator, and norethisterone, a synthetic progestogen, are commonly used in its medical management. Objective of this study was to evaluate and compare the efficacy and safety of ormeloxifene and norethisterone in the management of AUB. Methods: A prospective comparative study was conducted on 100 women aged 35 years and above diagnosed with AUB at D. Y. Patil Hospital, Navi Mumbai between July 2023 to December 2024. Participants were randomly assigned to two treatment groups. Group A received ormeloxifene (60 mg twice a week for 12 weeks, then once weekly for four weeks), while Group B received norethisterone (5 mg twice daily from day 5 to 25 of the menstrual cycle for 4 cycles). The primary outcome was the change in PBAC score. Secondary outcomes included hemoglobin levels, endometrial thickness, and incidence of side effects, evaluated at baseline, 2 months, and 4 months. Results: Group A showed a 76.15% reduction in PBAC score, a 2.91 g/dl increase in hemoglobin, and a 4.09 mm decrease in endometrial thickness. In contrast, Group B demonstrated a 45.97% reduction in PBAC score, a 1.31 g/dl increase in hemoglobin, and a 3.50 mm decrease in endometrial thickness. Acne and gastrointestinal side effects were more common in the norethisterone group. Conclusions: Ormeloxifene was more effective and better tolerated than norethisterone for the treatment of AUB. Its weekly dosing schedule, superior hematological improvement, and lower side-effect profile make it a preferable first-line therapy.